Application of Internet of Things (IOT) in paddy and oil palm sector in Malaysia / Imnie Fadzlan Mat Jani and Zareen Zulkifli - Mat Jani, Imnie Fadzlan; Zulkifli, Zareen (Faculty of Plantation and Agrotechnology, 2018)
The Industrial Revolution was the improvement from the old manufacturing to the better manufacture processes. Involvement of internet in every sector are leading to the development of a country and achieving the vision of industrial revolution which is reducing manpower used. In Malaysia, agriculture are the next major contributor to the country after engineering sector. There are four major crop plantation in Malaysia and two of them are paddy and oil palm which are the commodity in international market. The global demand of rice and palm oil cannot be fulfil if our country are still fully depends on labour force and it will give a huge impact to the economy of our country. There are several components of IOT and the technology are facilitate farmers to get high production but are not practically applied by farmers in Malaysia. This study was conducted to study the components and technology of IOT in agriculture sector and its application in paddy and oil palm plantation which help farmers to gain high yield without involving high manpower. The implementation of Drone in paddy helps farmers to get uniform spraying of pesticide while the application Soil EC Mapping help farmers to collect information of soil before planting and both of this technology help them to reduce the usage of manpower. This is the reason why Malaysia should emphasize this application of technology to raise the productivity of agricultural sector that are so lacking in this country.